2008
DOI: 10.1080/13803390802014594
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and cognitive functions associated with cardiovascular disease in the elderly

Abstract: This study examines the relationship between systemic vascular function, neurocognitive performance, and structural brain abnormalities on magnetic resonance imaging (MRI) among geriatric outpatients with treated, stable cardiovascular disease and no history of neurological illness (n = 88, ages 56-85 years). Vascular function was assessed by cardiac ejection fraction and output, sequential systolic and diastolic blood pressures, flow mediated brachial artery reactivity (BAR), and carotid intima media thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 77 publications
5
90
1
Order By: Relevance
“…The system is involved in regulating attention, switching attentional focus, and task preparation 42 and is known to be affected early in the development of vascular cognitive impairment. [43][44][45] This interpretation is supported by our present finding that greater task-related BOLD response in these regions was associated with better task performance and faster reaction times. The cross-sectional nature of our study limits our ability to infer future cognitive trajectories from the observed functional activation changes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The system is involved in regulating attention, switching attentional focus, and task preparation 42 and is known to be affected early in the development of vascular cognitive impairment. [43][44][45] This interpretation is supported by our present finding that greater task-related BOLD response in these regions was associated with better task performance and faster reaction times. The cross-sectional nature of our study limits our ability to infer future cognitive trajectories from the observed functional activation changes.…”
Section: Discussionsupporting
confidence: 80%
“…Support is provided by a growing body of literature documenting that peripheral cardiovascular dysfunction is related to poor cerebrovascular health and diminished cognitive function in older patients with cardiovascular disease. [43][44][45][51][52][53][54][55] Due to the multifaceted nature of MetS, further research is necessary to explore the contributions of frank vascular disease to the observed cognitive taskϪrelated BOLD response changes in midlife. Further exploration of other potential mechanisms such as alterations in cerebral glucose metabolism and inflammation will also be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that these results provide supporting evidence for the efficacy of LLLT in improving cognitive performance as well as mood. Since the frontoparietal networks responsible for sustained attention appear to be particularly vulnerable to damage related to cardiovascular and metabolic disorders [29], LLLT may be a viable treatment alternative in those patient populations as well, especially in cases where restoring the original cardiovascular status is not feasible. Future studies should extend knowledge in this area by examining the effects of LLLT in middle-aged and older participants at varying degrees of risk for developing cardiovascular and cerebrovascular disorders including vascular cognitive impairment.…”
Section: Nonexercisementioning
confidence: 99%
“…Successful completion of this task requires intact visual function, attention, executive function, and auditory rehearsal and brain regions traditionally activated during successful completion of the task include bilateral frontal cortex, bilateral parietal lobe regions, and supplementary motor areas [27]. We chose this task as the cognitive challenge in our studies because working memory is known to activate brain areas susceptible to damage in metabolic syndrome [28] as well as cardiovascular diseases such as hypertension and coronary artery disease [29].…”
Section: Early Markers Of Brain Vulnerabilitymentioning
confidence: 99%
“…Patients at higher risk for neurocognitive deterioration (e.g. with diabetes or pre-existing cerebrovascular problems) [92][93][94] should be critically evaluated, involving neurologists for neurocognitive assessments. An important region for neurocognitive function is located in the hippocampus and current research includes investigating hippocampal-sparing cranial irradiation to reduce neurocognitive dysfunction [95,96].…”
Section: Prophylactic Cranial Irradiationmentioning
confidence: 99%